Effect of leukoreduction and pathogen reduction on the hemostatic function of whole blood. (13th April 2019) - Thomas, Kimberly A.; Shea, Susan M.; Yazer, Mark H.; Spinella, Philip C.
Abstract : BACKGROUND: There is renewed interest in the use of whole blood (WB) for resuscitation of patients in hemorrhagic shock. Leukoreduction with platelet‐sparing filters and pathogen reduction may be used to improve the safety profile of WB, yet the effects of leukoreduction and pathogen reduction on WB hemostatic function are not well characterized. STUDY DESIGN AND METHODS: Blood from 32 healthy group O donors was divided into treatment groups (n = 8 for each group): untreated, pathogen reduced (PR + ), leukoreduced using an in‐line filter (LR + ), or PR + LR + . Units were stored without agitation for 21 days between 1° and 6°C, with sampling on days 0 (pre‐ and post‐treatments), 1, 3, 5, 10, 15, and 21 for hemostatic function as assessed by thromboelastometry, thrombin generation, platelet activation factors, and platelet impedance aggregometry. RESULTS: From day 3 (D3) to D15 of storage, platelet count was reduced in PR + /LR + units compared to PR − /LR − units. From D10 to D21 of storage, maximum clot firmness (MCF) was reduced in PR + /LR + units compared to PR − /LR − units. From D3 to D21 of storage, platelet aggregation was reduced in PR + /LR + units compared to PR − /LR − units. Total thrombin generation was similar in all groups from D0 to D21. CONCLUSIONS: The combination of LR with a platelet‐sparing filter and PR significantly reduces hemostatic function compared to either treatment alone or untreated WB. The clinical consequences of LR and PR of WB in patients with severe bleeding should be examined in trials before both are used in combination in patients.